উন্নয়ন ও অর্থনীতি, প্রসঙ্গে বাংলাদেশ - আলী, মুহম্মদ মাহবুব (ঢাকা : ঐতিহ্য, 2001)
Economic development in Bangladesh and policy perspectives of the government.
Includes statistics.
বিবলিওগ্রাফী অন্তর্ভুক্ত।
ESS
Complimentary copy from Professor Dr. Nasreen Khundker
In Bengali.
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Economic policy